Rancang Bangun Alat Pemotong Daging Sapi Untuk Sate - , Moehamad Helmy Fauzi; Arifin; Jojo Sumarjo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This research focuses on the design and construction of a beef cutting tool specifically aimed at improving the efficiency and productivity of satay vendors. The tool utilises a 1/4 hp electric motor to drive a 10